Adsorption and Desorption Characteristics and Purification of Isoflavones from Crude Soybean Extract Using Macroporous Resins - Thi Ngoc Thu Tran; Xuan Vung Bui; Nguyen Thi Truc Loan; Nguyen Huu Thuan Anh; Truong Dang Le; Thi Minh Hanh Truong (Polish Journal of Food and Nutrition Sciences)
Isoflavones in soybean have been well-known with many health-promoting effects on humans. This study aimed to purify isoflavones from the crude soybean extract by the static adsorption/desorption process on macroporous resins. A screening test of four commercial resins: D101, AB-8, Amberlite (R) XAD4, and Diaion HP20 according to their adsorption/desorption characteristic for isoflavones was investigated. All four resins showed high adsorption and desorption characteristics in which D101 resin was chosen as the most suitable resin for purifying isoflavones. Compositional analysis showed that daidzin and genistin were the main isoflavones in the crude soybean extract. The adsorption isotherms data of total isoflavones, daidzin, and genistin fitted well with the Langmuir model with R 2 >0.98. The dynamic adsorption conditions for the purification process of isoflavones on the D101 resin-packed column were selected at the bed volume (BV) of 200 mL, feed volume of 3.75 BV, and flow rate of 1.5 BV/h. The dynamic desorption was carried out with the elution solution of 70% ( v/v ) ethanol, elution volume of 2.5 BV, and flow rate of 1 BV/h. The total isoflavone content in the purified extract was 8.70-fold higher than its initial content in the crude soybean extract with a recovery yield of nearly 80%. The study results reveal a strong possibility for large-scale production of isoflavones for further application in functional food products or pharmaceutical products.